Enhancing the Resilience of F&B MSMEs Through Mitigating Environmental Uncertainty Risks - Muzakar Isa; Siti Aisyah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2026)
The food and beverage (F&B) industry faces significant challenges in risk management due to the unpredictable quality of internal and external environments. This study aims to classify various types of risks and analyze risk management to improve the resilience of the F&B MSME supply chain. This study was conducted in Surakarta City, Indonesia, involving 250 F&B MSME business units, representing approximately 41.12% of the total MSME population. A total of 20 types of risks were classified into 4 groups using a structural model. MICMAC analysis was used to analyze the role of each type of risk. The interactions of 20 types of risks were classified by MICMAC analysis into four groups: linkage, autonomous dependent, and independent, and identify the types of risks that are relatively critical in the system. The findings of this study provide a clear framework for MSMEs to understand the risks they face and how these risks interact in the system. MICMAC analysis categorizes the many risk types inside the system to aid in the development of suitable mitigation strategies. This study provides a comprehensive understanding to MSMEs on how risks can be managed effectively and serves as a basis for further exploration. The novelty lies in the integration of vulnerability analysis and MICMAC-based risk classification in the context of F&B MSMEs. MICMAC analysis offers clear insights for researchers and MSMEs to understand complex risks.